TINJAUAN SOSIOLOGIS SASTRA DALAM PUISI "SYAIR ORANG LAPAR" KARYA TAUFIQ ISMAIL - Farhan Firman Muntako (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literary works always contain the writer's view of reality. The reality is processed and digested into a view or criticism of life. One type of literary work that contains a view of reality is his poem Taufiq Ismail entitled "The Poetry of Hunger People". The purpose of this research is to find out the meaning of social impact in Taufiq Ismail's poem entitled "Poetry of Hunger People". The poem contains the effects that occur when a situation befall on humans. It is hoped that this study can make us more sensitive to conditions and conditions. The reason for choosing his poem, Taufiq Ismail, is because the language is straightforward and concrete. With poetry that is straightforward and concrete, meaning can be sharp and comprehensive. The poem is analyzed on aspects of social impact that occur in a phenomenon. This research uses qualitative. The technique used is descriptive analysis technique. Researchers position themselves as a single instrument. The process is through noting things that are related to aspects of social impact. The results of this study indicate that in his poem Taufiq Ismail entitled "The Poetry of Hunger People" contains about 3 social impacts, namely: 1) not ready to face drought, 2) the lack of means of expressing freedom, and 3) the consequences of natural disasters. Based on these conclusions the researchers drew the common thread that natural disasters cannot be avoided but as humans can prepare themselves to face disasters in terms of their social. Keywords: social impact, literary sociology, poetry